2013
DOI: 10.5489/cuaj.1387
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic scrotal calcinosis: A rare entity and a review of the literature

Abstract: Scrotal calcinosis is a rare condition with presentation including intradermal nodules varying in size and number. Differentials include calcification of epidermal or pilar cysts noted by the presence of keratinaceous debris. We present 2 cases of scrotal calcinosis at our institution. IntroductionIdiopathic scrotal calcinosis (ISC) was first described in 1883 by Lewinski. 1 The clinical presentation of ISC includes gradual growth of brown-yellow, firm solitary or multiple nodules on the scrotal skin. This rar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 12 publications
0
27
0
1
Order By: Relevance
“…4 More recently, it has been suggested that they are the result of dartos muscle necrosis and degeneration with resulting dystrophic calcification of the dartos muscle. 5 Regarding our patient with family history of the same complained, study found no literature mentioned genetic as an etiology.…”
Section: Discussionmentioning
confidence: 70%
“…4 More recently, it has been suggested that they are the result of dartos muscle necrosis and degeneration with resulting dystrophic calcification of the dartos muscle. 5 Regarding our patient with family history of the same complained, study found no literature mentioned genetic as an etiology.…”
Section: Discussionmentioning
confidence: 70%
“…SC is a rare disease of the scrotal skin which usually presents with multiple asymptomatic, calcified nodules; lesions are usually ignored initially and patients commonly seek the clinician's opinion years or decades after the initial onset 2. Only a few hundred cases have been reported worldwide to date 3.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis can be easily confirmed by depiction of the calcific content of the nodules on radiography (Figure ). Although this condition is commonly asymptomatic, surgery is indicated for cosmetic reasons …”
Section: Focal Thickeningmentioning
confidence: 99%